Juvenile Myoclonic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 1994)
Video-polygraphic analyses of 302 myoclonic seizures (MS) in 5 patients with juvenile myoclonic epilepsy (JME) are reported from the Department of Pediatrics, Tokyo Women’s Medical College, Japan.